Prawo. O wieloznaczności pojęcia - Bekrycht, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The subject of this article is the analysis of law’s and norm’s term ambiguity. The content of the article focuses on presentation of interrelationship between normative systems as positive law, nature law, ethic and customs. The author shows a difference between two fundamental law’s origins which shape individual normative orders. He also presents in details their mutual influence and discusses the place of positive law against a background of other normative orders.